Структура популяцій Daphne laureola L. на межі їх ареалу - Расевич, В.В.; Дідух, Я.П. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Рассмотрены 23 ценопопуляции D. laureola, их возрастная, пространственная, жизненная структуры в соответствии с экологическими условиями произрастания. Исследованы численность, плотность, онтогенетический спектр и консортивные связи. Проанализированы различия и сходство растений Крыма и Марокко по структуре листовой пластинки и побегов (17 признаков). Установлено, что возрастные спектры ценопопуляций Крыма неполночленные, правосторонние, несмотря на достаточно большую среднюю плотность (0,95 особи/м2). Виталитетная структура популяций в пределах класса Erico - Pinetea выше, чем класса Quercetea - Pubescenti petraea. Количественный анализ параметров листовой пластинки не подтвердил отличия между D. laureola subsp. laureola из Крыма и D. laureola var. latifolia с гор Атласа. The structures of 23 D. laureola populations are given: age, spatial, vitality in the ratio with the ecological factors which situated on plants habitat. Were investigated: numberity, density, ontogenetic spectrum and consorts connection of populations. Was carried out analysis on a different and similarity of Daphne plants from Crimea and Morocco. For this proper authors used structure of leaves plate and branches (17 parameters). Age populations spectra from Crimea are not complete and generally with right-hand type. On other side average density of specia 0,95 plants/m2. The vital structure of populations in borders of a Cl Erico-Pinetea is higher than Cl Quercetea-Pubescenti petraea. Quantitative analysis of leaves flat parameters has not confirmed difference between D. laureola subsp. laureola from Crimea and D. laureola var. latifolia from Atlas mountains.